VEGETABLE OILS FOR HIGH VOLTAGE INSULATION BY (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper discusses the findings of the study of the possibility of using some vegetable oils as high voltage insulation materials. Samples of palm oil (elaeis guineensis), palm kernel oil (elaeis guineensis), coconut oil (cocos nucifera), groundnut oil(Arachis hypogea) and local pear oil(dacryodes edulis) were obtained from Ekwulobia town, processed and tested. The results obtained showed exciting performance for palm oil, palm kernel oil and groundnut oil. Investigation on the dielectric strength of local pear oil (dacryodes eduli) is inconclusive because the sample collected was not sufficient for the tests.